Cost pass-through of the EU emissions allowances: Examining the European petroleum markets - Victoria Alexeeva-Talebi (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper explores the ability of European refineries to pass-through costs associated with the introduction of the EU Emissions Trading Scheme (EU ETS). We estimated a sequence of vector error correction models (VECM) within a multi-national setting which covers 14 EU member states. Using weekly data at the country level, this paper finds a significant influence of prices for European Union Allowances (EUAs) on unleaded petrol retail prices during the trial phase of the EU ETS from 2005 to 2007. Petrol prices are found to be elastic with respect to crude oil prices and exchange rates but rather inelastic with respect to carbon costs. The long-run elasticity of petrol prices with respect to the EUA prices typically ranges between 0.01% and 0.09%. Furthermore, by computing the variance decomposition our analysis shows that a significant fraction of petrol price changes in Austria, Germany, France and Spain can be explained by changes in allowances prices (between 10% and 20%).
Keywords: F18; C22; L11; 330; Cost Pass-Through; Emissions Trading Scheme; Refineries; Emissionshandel; Umweltschutzkosten; Betriebliche Preispolitik; Erdölraffinerie; Benzin; Preiselastizität; Schätzung; EU-Staaten